A novel thermal exfoliation strategy for the fabrication of high-quality Ag/TiO2 nanosnowman nanoparticles with enhanced photocatalytic properties. (26th March 2018) - Zhang, Chao; Zhou, Yuming; Bao, Jiehua; Zhang, Yiwei; Sheng, Xiaoli
Abstract : A novel thermal exfoliation strategy has been proposed to synthesize high-quality Ag/TiO2 head–body nanosnowman nanoparticles (AgTiNPs, with the head and body being single Ag and TiO2 nanoparticles, respectively). Abstract : A novel thermal exfoliation strategy has been proposed to synthesize high-quality Ag/TiO2 head–body nanosnowman nanoparticles (AgTiNPs, with the head and body being single Ag and TiO2 nanoparticles, respectively) for the first time. The obtained samples were characterized with transmission electron microscopy (TEM), X-ray photoelectron spectra (XPS) and photoluminescence (PL) emission spectra, etc. Results show that loaded Ag nanoparticles could exfoliate with a part of an adjacent caducous TiO2 nanosheet during calcination treatment, thereby fabricating high-quality Ag/TiO2 head–body nanosnowman nanoparticles. The prepared AgTiNPs show a uniform particle size, a high dispersion and enhanced interactions between Ag heads and TiO2 bodies. Compared with calcined Ag/DHS, AgTiNPs exhibit an enhanced photocatalytic performance in the degradation of RhB and solar H2 production due to improved charge carrier separation. The proposed thermal exfoliation strategy might open up a new method for the fabrication of other semiconductor–metal nanosnowman nanoparticles with enhanced photochemical properties.